New data about stratigraphy and structure of the Vila Velha de Ródão complex syncline, SW sector of the Central-Iberian Zone, Portugal - Metodiev, Daniel (2010)
New data about the lithostratigraphy and the progressive Variscan structure of the Vila Velha de Ródão complex syncline is presented. During the geological mapping revision was established an Ordovician-Silurian succession, very similar to the Amêndoa-Carvoeiro synform DJ (Romão, 2000). The Variscan deformation includes: early overthrusts subsequently transformed in forethrusts with duplex geometry facing to NE, folds, cleavage and linear structures (D1a and D1b) and latter crenulation, backthrusts and backfolds with anopposite facing (D1c). Their compatible progressive deformation with NE-SW maximum compression induces decollement in depth of thin-skinned type and creates triangular structures. This macrostructure is affected by late-Variscan faults, probably associated with a domino structures, of which the most important is the Ponsul reverse fault.